Influence of flavanone on the stabilization of ethylene-propylene elastomer - Zaborski, M.; Masek, A.; Chrzescijanska, E. (Polimery, 2011)
Antioxidating properties of flavanone were investigated with electroanalytical methods. Voltamperograms of flavanone oxidation on the Pt electrode reveal that along with increasing polarization rate the peak potential shifts slightly towards more positive potentials. The dependence of the peak current on the square root of the polarization rate is linear and the plot of the function passes through the origin of coordinates, which indicates no adsorption of the investigated substrate on the electrode and a diffusive control of the studied electrode reaction. To the ethylene-propylene elastomer (EPM) there were added 1.25 phr of flavanone and there was studied its impact on the stability of these blends subjected to thermal ageing and UV irradiation. The antioxidating efficiency of the investigated antioxidizer was established from changes in the deformation energy, crosslinking density and color of the EPM vulcanizates. Based on the results obtained, it was stated that flavanone performs its function well, providing good protection of the vulcanizates from oxidative processes.